Utilization of plastic waste using the ecobrick method in Nagari Tanjung - Dony Novaliendry; Muhammad Devin Rahadi; Ilsa Amalinda; Jumaita Lestari; Nurul Aieni; Vanisa Tsuraya Yahmanita; Kharisa Ramadhani; Kiki Ardika (Privietlab, 2025)
Pollution caused by the continued practice of dumping waste into the river and burning it has become a serious problem in Nagari Tanjung, Koto VII Subdistrict, and Sijunjung Regency. The community and village government have not felt sufficiently supported by the existence of a final disposal site (TPA), so residents—especially housewives—dispose of waste around the river, and some residents burn it. This has led to pollution and negative health and environmental effects. Therefore, a community service program was implemented that involved educating the community on waste management and hands-on practice in making ecobricks as a practical approach to utilizing plastic waste. The program ran for three weeks, from June 19, 2025, to July 10, 2025, in Jorong Ujung Padang, involving 44 participants from the beneficiary community members, nagari officials, and students. Throughout the implementation, the activities were guided and facilitated by two supervising lecturers. The stages included delivering material on the importance of waste management, training on Ecobricks production, and mentoring in applying environmentally friendly concepts. The results showed increased community awareness in managing plastic waste and the successful production of 100 ecobricks, which were used as garden elements.